3D dynamic simulation and visualization for GIS-based infiltration excess overland flow modeling - Mohamad Yusoff, Izham (Penerbit UTM, 2008)
Effective GIS-based Infiltration Excess Overland Flow (IEOF) simulation and visualization requires good knowledge of GIS core concepts and prediction of soil infiltration rates due to impervious area coverage. The success or failure of GIS-based IEOF simulation and visualization resides initially with the georeference system used. Cartographers have long complained about the poor quality of the output from GIS, which today is generally due not to limitations of the GIS itself but instead to a lack of understanding of cartographic principles among hydrologists and environmentalists. Implementation of soft geo-objects representing flow elements such as streams, mudflows, and runoff provides better dynamic visualization in terms of velocity and direction. Inclusion of volumetric overland flow would help in determining the volume of runoff that hits the flood-plain areas, estimating channel flow capacity, and routing and diversions to reduce effects from flooding. With rapid urbanization, industrialization, and climate change, historical runoff and infiltration rates would provide an improper guide for future enhanced visualization of the current 2D land use surface. This study aims to visualize the influence of georeferencing on IEOF simulation when represented by volumetric soft geo-objects within a 3D environment, which is driven by the physically based Green-Ampt method. Visualization is analyzed by focusing on infiltration and overland flow processes using the conformal-based Malaysian Rectified Skew Orthomorphic (MRSO) and the equidistant-based Cassini-Soldner projection. Appropriate usage of a georeferencing system to visualize 3D dynamic IEOF simulation may see high demand from civil engineers, environmentalists, town planners, geologists, and meteorologists as a basis for producing scientific results in flood management control, sustainability for long-term development purposes, stream restoration, rehabilitation, and hydrologic impact assessment.